Analysis on influencing factors of readiness for hospital discharge among patients with liver cancer under the concept of enhanced recovery after surgery (加速康复外科模式下肝癌患者出院准备度影响因素分析) - WANG Jing (王静); CHEN Li (陈莉) (Association of Integrative Nursing, 2021)
Objective To investigate the status of readiness for hospital discharge(RHD)of patients with liver cancer under the concept of Enhanced Recovery After Surgery (ERAS), analyze its influencing factors, and provide the basis for regulating the discharge guidance. Methods Totally 128 patients with liver cancer were selected as the research object, and patients were investigated by using the general data questionnaire, the Readiness for Hospital Discharge Scale(RHDS) and the Quality of Discharge Teaching Scale(QDTS). Results The total score of RHDS was 146. 82±28. 69, and 75. 00%(96/128) of the patients were prepared for discharge. The results of univariate analysis suggested that age, place of residence, occupation, operation mode, per capita income of the family and the quality of discharge teaching were influencing factors of discharge preparation. The results of multivariate analysis suggested that age, residence, occupation and quality of discharge teaching were the independent factors affecting discharge readiness. Conclusion Under the under the concept of ERAS, the level of RHD for patients with liver cancer needs to be further improved, and medical staff should adopt various forms to strengthen the discharge preparation service, improve the quality of discharge guidance for specific target population, and focus on the elderly discharged patients. (目的 调查加速康复外科(ERAS)模式下肝癌患者的出院准备度(RHD)现状, 并分析其影响因素, 为规范患者出院指导提供依据。方法 采用一般资料调查表、出院准备度量表(RHDS)、出院指导质量表(QDTS)对128例肝癌患者进行调查, 并对结果进行分析。结果 ERAS模式下肝癌患者的出院准备度总分是(146. 82±28. 69)分, 75. 00%(96/128)的患者做好出院准备。单因素分析显示, 年龄、居住地、职业、手术方式、家庭人均月收入和出院指导质量是影响患者RHD的因素。多因素分析显示, 年龄、居住地、职业和出院指导质量是影响患者RHD的主要因素。结论 ERAS模式下, 肝癌患者RHD水平需进一步提高, 医护人员应采用多种形式加强出院准备服务, 针对特定目标人群提高出院指导质量, 重点关注老年出院患者。)